Implementasi Etika Islam (Ilmu Hal) dalam Kitab Ta'lim Al-Muta'allim: Strategi Pembinaan Akhlak Santri di Pondok Pesantren Hidayatul Qur'an Singosari - Ahmad Marzuki; Moh. Nadhif (STAI Ma'had Aly Al-Hikam Malang, 2025)
This research is motivated by the phenomenon in contemporary Islamic education where many people have knowledge but do not practice it (al-'alim ghairu al-'amil), so Ilmu Hal as a religious foundation that includes akidah, fiqh, and morals becomes a strategic solution to shape the character of santri. This study aims to analyze the implementation of Ilmu Hal from the book of Ta'lim al-Muta'allim in shaping the character of students and identify the supporting and inhibiting factors at Hidayatul Qur'an Islamic Boarding School in Singosari Malang. With a descriptive qualitative approach and case study method, data were collected through in-depth interviews with 10 informants (ustadz and santri), participatory observation, and document study, then analyzed interactively through data reduction, data presentation, and verification. The results showed that the implementation of Hal Science is realized in four domains: (1) to God through orderly worship such as congregational prayer and recitation of the Qur'an, (2) to teachers through respect and obedience, (3) to fellow students through social solidarity, and (4) to society through polite communication, with the main supporting factors in the form of exemplary ustadz and positive habituation, while the main inhibiting factor is the influence of a less conducive external environment.